Travels in Bosnia by Ivan Lovrenović - Kaniecka, Dominika (Poznańskie Studia Slawistyczne, 2024)
In this article, I describe interactions between space and literature trough the example of texts by the writer and intellectual from Sarajevo, Ivan Lovrenović. It is important for this analysis that the journey was undertaken by a person with specific interests and competences, and that it was a real journey to places that exist or really existed. I discuss the analyzed problems by referring to selected research fields of geopoetics. I read Ivan Lovrenovic’s book Ikavski zemljopis as “auto/bio/geo/graphy”. I am interested in recreating fragments of the spatial frame of a traveler’s autobiographical memory, sensory perception of specific places, emotions accompanying the experience of space, as well as the tension between history, memory (both individual and collective) and writing. His literary maps are a rescue for Bosnia and Hercegovina, whose multiculturalism is slowly disappearing, or a farewell to such a dimension. The texts of Ivan Lovrenović indicate important places of memory to those who do not see them, becoming an important “place of memory” themselves.